2017
DOI: 10.1007/s00204-017-2147-y
|View full text |Cite
|
Sign up to set email alerts
|

The formation of estrogen-like tamoxifen metabolites and their influence on enzyme activity and gene expression of ADME genes

Abstract: Tamoxifen, a standard therapy for breast cancer, is metabolized to compounds with anti-estrogenic as well as estrogen-like action at the estrogen receptor. Little is known about the formation of estrogen-like metabolites and their biological impact. Thus, we characterized the estrogen-like metabolites tamoxifen bisphenol and metabolite E for their metabolic pathway and their influence on cytochrome P450 activity and ADME gene expression. The formation of tamoxifen bisphenol and metabolite E was studied in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Although there is not much evidence in the literature that ENDO could be metabolized by CYP3A4, it has been suggested that norendoxifen, another metabolite of TAM, could be formed via N‐demethylation of ENDO, which is a phase I reaction involving CYP isoenzymes . In addition, a recent in vitro study showed that an estrogen‐like metabolite of TAM (bisphenol tamoxifen) can be formed from ENDO in presence of CYP3A4 . More studies are needed to investigate the relative implication of CYP3A4 in ENDO metabolism compared with other enzymes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although there is not much evidence in the literature that ENDO could be metabolized by CYP3A4, it has been suggested that norendoxifen, another metabolite of TAM, could be formed via N‐demethylation of ENDO, which is a phase I reaction involving CYP isoenzymes . In addition, a recent in vitro study showed that an estrogen‐like metabolite of TAM (bisphenol tamoxifen) can be formed from ENDO in presence of CYP3A4 . More studies are needed to investigate the relative implication of CYP3A4 in ENDO metabolism compared with other enzymes.…”
Section: Discussionsupporting
confidence: 89%
“…23,24 In addition, a recent in vitro study showed that an estrogen-like metabolite of TAM (bisphenol tamoxifen) can be formed from ENDO in presence of CYP3A4. 25 More studies are needed to investigate the relative implication of CYP3A4 in ENDO metabolism compared with other enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…23 Future studies should expand research efforts on comprehensive understandings of TAM functions in cancers. It is interpretable that TAM might have some metabolites with oestrogen-like action at the oestrogen receptor.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Since TAM could inhibit cell growth by inhibiting glycolysis, we It is quite reasonable because plenty of studies indicated low concentration TAM treatment show slight oestrogen-like activity in short time.…”
Section: Tam Suppresses Gbc Viability Via Impaired Glycolysismentioning
confidence: 99%
See 1 more Smart Citation